Optimization method for predicting coal reservoir fractures in the Laochang area of Eastern Yunnan using paleotectonic stress inversion - Wu, Changwu; Wang, Bo; Hu, Xiong; Jin, Xue; Liang, Wei; Shi, Mingjian; Zhu, Xueguang; Guo, Liang (Frontiers in Earth Science, 2024)
IntroductionCoal reservoir fractures serve as critical storage spaces and migration pathways for coalbed methane (CBM), significantly influencing CBM enrichment. The characteristics of coal reservoir fracture development can be obtained using traditional simulation methods, but these still have shortcomings. This work presents an optimization approach for the traditional method.MethodsThis study introduces an optimization approach for traditional methods with two novel contributions. This study integrates the simulation of tectonic stress fields with fracture prediction, using surface sandstone fractures as constraints to reconstruct the paleostress field of the coal seam, while also accounting for the influence of coal thickness on fracture development to calculate fracture density.ResultsThe predicted fracture density results were validated against measured values from the Bailongshan mine and Xiongdong coal mine with a relative error of approximately 12%, suggesting a reasonable degree of reliability.DiscussionBased on the results of the fracture simulation predictions, it is believed that the coal seam fracture density in the study area is mostly 10–20 lines/m and that the sweet spot for CBM development is located in the Yuwang block.